Acheson and empire : the British accent in American foreign policy - McNay, John T., 1957- (University of Missouri Press, 2001)
"Acheson and Empire offers a reassessment of Dean Acheson's policies toward the former colonial world during his period as secretary of state from 1949 to 1953. John T. McNay argues that Acheson inherited through his own personal history a way of understanding the world that encouraged imperial-style international relationships. This worldview represented a well-developed belief system rooted in his Ulster Protestant heritage that remained consistent throughout his life." "By exploring relationships of the United States with Britain and countries formerly or then controlled by Britain, such as India, Ireland, Iran, and Egypt, McNay shows the significance of Acheson's beliefs. McNay argues that Acheson's support of existing imperial relationships was so steadfast that it often led other nations to perceive that the United States was nothing more than a front for British interests. He believes this approach to foreign policy damaged American relations with emerging countries and misled the British regarding possibilities of an Anglo-American partnership." "Acheson and Empire contends that the widely accepted view of Acheson as a foreign policy realist is misleading and that historians should acknowledge that his affinity for the British Empire went beyond his clothing and mannerisms. McNay maintains that the widely accepted view of Acheson as one of a group of "wise men" who shaped the Cold War world by basing their decisions on cold calculation of American interests should be reconsidered."--Jacket